Every spy a traitor / Alex Gerlis. - Gerlis, Alex (Double agent series., 2024)
It's 1937. Fear and suspicion stalk the Continent. A million have died in Stalin's Great Purge and the Nazi terror grips Germany. But British intelligence is still trying to work out who the enemy is. As Europe heads towards war, treason is in the air. British spymasters know there is one Soviet agent in their ranks, codenamed Agent 'Archie', and there's a frantic search to find them. What they don't know is that he is not the only traitor. The life of Charles Cooper, a young British writer travelling Europe to research his novel, is about to change for ever.